The Angiotensin-(1-7)/Mas Axis Counteracts Angiotensin II-Dependent and -Independent Pro-inflammatory Signaling in Human Vascular Smooth Muscle Cells - Villalobos, Laura A.; San Hipólito-Luengo, Álvaro; Ramos-González, Mariella; Cercas, Elena; Vallejo, Susana; Romero, Alejandra; Romacho, Tania; Carraro, Raffaele; Sánchez-Ferrer, Carlos F.; Peiró, Concepción (Frontiers in Pharmacology, 2016)
Background and aims: Targeting inflammation is nowadays considered as a challenging pharmacological strategy to prevent or delay the development of vascular diseases. Angiotensin-(1-7) is a member of the renin-angiotensin system (RAS) that binds Mas receptors and has gained growing attention in the last years as a regulator of vascular homeostasis. Here, we explored the capacity of Ang-(1-7) to counteract human aortic smooth muscle cell (HASMC) inflammation triggered by RAS-dependent and –independent stimuli, such as Ang II or interleukin (IL)-1. Methods and Results: In cultured HASMC, the expression of iNOS and the release of nitric oxide were stimulated by both Ang II and IL-1, as determined by Western blot and indirect immunofluorescence or the Griess method, respectively. iNOS induction was inhibited by Ang-(1-7) in a concentration-dependent manner. This effect was equally blocked by two different Mas receptor antagonists, A779 and D-Pro7-Ang-(1-7), suggesting the participation of a unique Mas receptor subtype. Using pharmacological inhibitors, the induction of iNOS was proven to rely on the consecutive upstream activation of NADPH oxidase and NF-B. Indeed, Ang-(1-7) markedly inhibited the activation of the NADPH oxidase and subsequently of NF-B, as determined by lucigenin-derived chemiluminiscence and electromobility shift assay, respectively. Conclusion: Ang-(1-7) can act as a counter-regulator of the inflammation of vascular smooth muscle cells triggered by Ang II, but also by other stimuli beyond the RAS. Activating or mimicking the Ang-(1-7)/Mas axis may represent a pharmacological opportunity to attenuate the pro-inflammatory environment that promotes and sustains the development of vascular diseases.